Vitamin D and Depression: The Evidence from an Indirect Clue to Treatment Strategy - Wong, Sok K.; Chin, Kok-Yong; Ima-Nirwana, Soelaiman (Current Drug Targets, 2018)
Depression is a common psychiatric disorder that decreases the quality of life and increases the mortality of patients. It incurs significant healthcare costs if left untreated. Even though intervention with antidepressants can reduce depressive symptoms, side effects are often an issue and relapse is very common. Vitamin D, commonly known as the sunshine vitamin, is an essential fat-soluble vitamin for the absorption of calcium to prevent rickets (children) and osteomalacia (adults). Evidence on a possible relationship between vitamin D deficiency and depression is growing. In this review, the authors summarized the evidence on the association between vitamin D status and depression in human observational studies, followed by clinical trials to evaluate the effects of vitamin D supplementation in treating depression. In conclusion, vitamin D deficiency may be associated with an increased risk or severity of depression. Supplementation of vitamin D may confer protection for depressed patients.
Keywords: mental health